A biosynthetic model of cytochrome c oxidase as an electrocatalyst for oxygen reduction - Mukherjee, Sohini (Nat Commun, 2015)
Creating an artificial functional mimic of the mitochondrial enzyme cytochrome c oxidase (CcO) has been a long-term goal of the scientific community as such a mimic will not only add to our fundamental understanding of how CcO works but may also pave the way for efficient electrocatalysts for oxygen reduction in hydrogen/oxygen fuel cells. Here we develop an electrocatalyst for reducing oxygen to water under ambient conditions. We use site-directed mutants of myoglobin, where both the distal Cu and the redox-active tyrosine residue present in CcO are modelled. In situ Raman spectroscopy shows that this catalyst features very fast electron transfer rates, facile oxygen binding and O–O bond lysis. An electron transfer shunt from the electrode circumvents the slow dissociation of a ferric hydroxide species, which slows down native CcO (bovine 500 s(−1)), allowing electrocatalytic oxygen reduction rates of 5,000 s(−1) for these biosynthetic models.